Evaluation of hematite and quartz flotation kinetics using surfactant produced by Rhodococcus erythropolis as bioreagent - Olivera,Carlos Alberto Castañeda (2019)
Abstract The use of biosurfactants as reagents represents a promising alternative to the conventional surfactants used in the mineral industry because they may present low toxicity and high biodegradability. Therefore, this research studied the hematite and quartz flotation kinetics using surfactant produced by Rhodococcus erythropolis as bioreagent. The flotation kinetics of both minerals were evaluated under established conditions: biosurfactant concentration of 10 mg/L and solution pH of 3. The maximum floatability values were of 99.98% and 17.53% for hematite and quartz, respectively, after 2 minutes of flotation. Finally, the kinetics study indicated that the experimental data of hematite floatability was better fitted to both the first and non-integral order kinetics, while the experimental data of quartz floatability was better fitted to the non-integral order kinetic.